2009
DOI: 10.1038/gt.2009.141
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of skeletal muscle in intact mice lacking myostatin by concurrent NMR imaging and spectroscopy

Abstract: Inhibiting myostatin (mstn) causes spectacular increase in muscle mass, spurring research for therapeutic approaches against neuromuscular disorders. Yet, possible functional deterioration and compromised force production have been reported in isolated muscle of null mstn(-/-) mice. We analyzed vascular and metabolic response to repeated electro-stimulated exercise in vivo in mstn(-/-) mice compared with FVB wild-type controls (WT), using interleaved multi-parametric functional nuclear magnetic resonance (NMR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 48 publications
(59 reference statements)
10
25
0
Order By: Relevance
“…One of the major findings of the present study is that long-term disruption of ActRIIB signaling impairs mitochondrial function in skeletal muscle, which is comparable to data obtained in myostatin-deficient animals (2,6,19,45). We found actually that sActRIIB-Fc treatment dramatically reduced the maximal rate of oxidative ATP synthesis (Ϫ42%), which is considered a robust and highly reproducible in vivo index of oxidative mitochondrial capacity and has been widely used in research and clinical applications (4,7,26,32).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One of the major findings of the present study is that long-term disruption of ActRIIB signaling impairs mitochondrial function in skeletal muscle, which is comparable to data obtained in myostatin-deficient animals (2,6,19,45). We found actually that sActRIIB-Fc treatment dramatically reduced the maximal rate of oxidative ATP synthesis (Ϫ42%), which is considered a robust and highly reproducible in vivo index of oxidative mitochondrial capacity and has been widely used in research and clinical applications (4,7,26,32).…”
Section: Discussionsupporting
confidence: 87%
“…It has been shown that postnatal disruption of ActRIIB signaling in normal mice improves functional parameters such as grip strength (1,33) and absolute force in isolated muscle (1,15) but on the other hand decreases resistance to fatigue (15,52). These results are in all respects comparable to those obtained in myostatin-deficient mice in which improved force has been documented (2,19,43,45) and the increased fatigability has been assigned to a mitochondrial impairment evidenced on the basis of in vitro assays (45,48) and in vivo 31 P-MRS measurements (6,19). Interestingly, long-term sActRIIB-Fc treatment in wild-type mice has been shown to reduce the expression of oxidative phosphorylation genes (50,52,60) as well as the level of porin, an outer mitochondrial membrane protein involved in ATP transport between the cytosol and the mitochondrial matrix (52).…”
supporting
confidence: 55%
“…In diabetes mellitus type 1, cardiolipin content is decreased in the IMF subpopulation, but not in the in the sub-sarcolemmal subpopulation [69,70]. The decrease in CL mitochondria content, demonstrated in our study, could thus lead to the uncoupling in the mitochondria respiration (decay in the respiratory ratio control in the IMF mitochondria) and the decrease in ATP production previously reported in mstn KO muscle [13,71]. Consequently, we propose that the significant decrease in CL in Mstn KO mice, pointing to a defect of IMF, as one causative mechanism for the metabolic phenotype.…”
Section: Accepted M Manuscriptsupporting
confidence: 51%
“…However, the potential benefit of Mstn deficiency on muscle function and energetics remains a matter of debate. It is undisputable that the increased muscle size induced by the lack of Mstn is linked to an enhancement of absolute force generation that has been observed in vivo or in vitro in various murine muscles such as soleus (26), extensor digitorum longus (EDL) (26), and triceps surae (6). Also, chronic administration of an inhibitory antibody of Mstn in adult mice increases skeletal mass and grip strength (35).…”
mentioning
confidence: 99%
“…However, the corresponding improvement in specific force (i.e., absolute force scaled to muscle size) remains controversial. As an illustration, specific force in mouse models lacking Mstn has been reported to increase in triceps surae electrostimulated in vivo (6), to remain unaffected in isolated soleus muscle (26), or even to decrease in EDL (4,26).…”
mentioning
confidence: 99%